PREVALENCE OF TYPE II DIABETES MELLITUS IN OBESE PERSONS - Alaa Anwer Ali (Zeta Repository, 2023)
Certain Near Eastern nations have some of the largest increases of insulin resistance and overweight, and this is reflected in the number of obese people within individuals with category 2 diabetes.. The purpose of this research was to determine how common overweight is among Iraqi individuals diagnosed with type 2 diabetic Participants' BMIs were taken on their initial visit to the endocrinologist and diabetic department at Saint Raphael (Al Rahibat) Hospital in Baghdad, Iraq among those 16 and older diagnosed with type 2 diabetes mellitus during a period of 4 years. It was shown that the incidence of type 2 diabetes mellitus was 21 (70%) amongst overweight, 19 (63%) among the obese, and 50 (18.7%) among the normal community. Total occurrence of type 2 diabetics was more significantly associated with obese category (20.2% vs. 15.5% in overweight; 2 = 0.969; P = 0.325). It was revealed that 20.2%, 22.2%, and 21% and 8.2% of the study population were affected by type 2 diabetes mellitus and hypertension, respectively, if they fell into the obese category. This demonstrates that both type 2 diabetes and high blood pressure are more prevalent when body mass index (BMI) increases in a population. The rate of type 2 diabetes and hypertension was higher than in previous studies done in India and abroad.